ASSESSMENT OF ADHESION TO TREATMENT OF PATIENTS BEING ON KIDNEY REPLACEMENT THERAPY TAKING INTO ACCOUNT THE PRESENCE OF TYPE 2 DIABETES MELLITUS - Katerenchuk, I.P.; Rustamian, S.T. (World of Medicine and Biology, 2021)
This article presents the results of the analysis of adherence to treatment of patients on renal replacement therapy, taking into account type 2 diabetes. It was found that the adherence index to treatment is directly proportional to the patient's age and does not depend on the article and duration of treatment on programmed hemodialysis. In turn, the presence of a history of diabetes increases patient compliance, which, in turn, has a positive effect on disease control by both the doctor and the patient. Patients with stage I-II chronic kidney disease have a low level of adherence, which may be an additional risk factor for renal failure progression.
Keywords: compliance; program hemodialysis; diabetes mellitus; chronic kidney disease